Viruses and STEAM: How to Introduce Preventing Disease Transmission in Children through STEAM-Based Learning Methods? - Syarfina, Syarfina; Yasmin, Aina; Fauziddin, Mohammad (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2022)
An introduction to preventing the transmission of diseases is not only essential during a pandemic because viruses are the closest part of the children. However, this is not easy to teach in early childhood, which is in a substantial period; interesting methods are needed and accepted by children's logic. This study aimed to describe the process of introducing ways to prevent disease transmission in children through learning methods based on Science, Technology, Engineering, Art, and Mathematics (STEAM). This qualitative research method was presented with a descriptive approach. Informants in this study were teachers who teach children aged 5-6 years at TPA Gampong Daulat, Langsa, Aceh. Researchers collected data through observation techniques. The data were analyzed in three stages: data reduction, data presentation and conclusion drawing. The results showed that the STEAM-based learning method was integrated into the concept and practice of health protocols. Ways of transmitting diseases caused by viruses in the form of washing hands, wearing masks, and keeping a distance taught based on the STEAM method make children actively involved and think logically and critically. The effectiveness of the STEAM-based learning method in teaching other aspects of health can be studied further.